UPAYA PENINGKATAN GIZI DAN PENCEGAHAN STUNTING DENGAN PUDDING KROKOT GENERASI SEHAT DESA SARIMULYO KECAMATAN JOMBANG - efrizal amrullah, akhmad (LPPM Universitas dr. Soebandi, 2025)
This study was motivated by the stunting phenomenon in Sarimulyo Village, Jombang District. Stunting or stunted growth in children is often caused by malnutrition. The aim of this research is to determine the benefits and contents of the portulaca oleracea which is processed into pudding to prevent stunting. In this research, the type of data used is qualitative data. Primary data and secondary data are data sources used in research. The data collection methods used in this research are interviews, observation, document study and literature study. The population used in this research was portulacea oleracea from the garden of one of the residents of Sarimulyo Village, and for the sample two stalks of portulaca oleracea were used. The phenomenological method is an analytical method used in research. The results of this research show that portulaca oleracea which are processed into pudding can prevent stunting in Sarimulyo Village, Jombang District